A Systematic Review of Father-Child Play Interactions and the Impacts on Child Development - Erin Louise Robinson; Jennifer StGeorge; Emily Elsa Freeman (MDPI AG, 2021)
Father-child play engagement has been linked to a variety of child developmental outcomes. However, the most prevalent types of play and child developmental outcomes utilised in research remains unclear. The aim of this study was to systematically review the literature on father-child play interactions and the association with child developmental outcomes for children aged 0-10 years. Database searches generated 1622 abstracts that matched the specified search criteria. Abstract screening and full-text review resulted in 39 included publications. The systematic review revealed that while some paternal play behaviours resulted in different impacts across play types, others reported similar impacts. The findings of this review have implications for potential interventions and parenting resources.